Homozygous Protein C Deficiency: Description of a New Mutation and Successful Treatment with Low Molecular Weight Heparin - Monagle, Paul; Andrew, Maureen; Halton, Jacqueline; Marlar, Richard; Jardine, Lawrence; Vegh, Patricia; Johnston, Marilyn; Webber, Colin; Massicotte, Patricia M. (Thrombosis and Haemostasis, 1998)
We present a kindred with a new mutation of the protein C gene, in which the proband had an unusual clinical presentation. The relationship between warfarin induced skin necrosis and level of anticoagulation was investigated. The pharmacokinetics of protein C concentrate was assessed to determine frequency of replacement therapy. The clinical and biochemical efficacy of therapy with low molecular weight heparin (LMWH) was assessed. The effect of long-term LMWH on bone density in the growing child was monitored using whole body densitometry.Warfarin therapy required an INR of greater than 3.5 to avoid skin necrosis. If protein C replacement was to be used, doses of 100 U/kg/day would have been required to maintain protein C levels consistently at or above 0.20 U/ml. While receiving prophylactic therapy with LMWH for almost 3 years, there were no episodes of recurrent thrombosis, no skin necrosis and no bleeding. Biochemical markers of in vivo thrombin generation were suppressed and within the normal range. Bone density continued to increase at the normal rate throughout the treatment period.LMWH is an effective form of long-term therapy for homozygous protein C deficient patients with measurable protein C levels.